2013
DOI: 10.1002/anie.201302406
|View full text |Cite
|
Sign up to set email alerts
|

LovG: The Thioesterase Required for Dihydromonacolin L Release and Lovastatin Nonaketide Synthase Turnover in Lovastatin Biosynthesis

Abstract: The cryptic thioesterase LovG is found to be responsible for product release from the lovastatin nonaketide synthase (LNKS or LovB). The same enzyme also helps improving turnover of LovB through hydrolysis of incorrectly tailored intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 22 publications
2
83
0
1
Order By: Relevance
“…The metabolite data were furthermore used to propose a model for fusarielin biosynthesis in F. graminearum (Figure 3) based on models for lovastatin biosynthesis [3,10,15]. Analyses of the fusarielin and lovastatin gene clusters showed that there is some sequence similarity for the PKS's (38% identity), trans-thioesterases (28% identity), and trans-ERs (46% identity), with E values from blastP analyses ranging from 0.0 to 1 × 10 −8 (Supplementary Table S1).…”
Section: Posmentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolite data were furthermore used to propose a model for fusarielin biosynthesis in F. graminearum (Figure 3) based on models for lovastatin biosynthesis [3,10,15]. Analyses of the fusarielin and lovastatin gene clusters showed that there is some sequence similarity for the PKS's (38% identity), trans-thioesterases (28% identity), and trans-ERs (46% identity), with E values from blastP analyses ranging from 0.0 to 1 × 10 −8 (Supplementary Table S1).…”
Section: Posmentioning
confidence: 99%
“…This suggest that there are several similarities to the biosynthetic pathway of lovastatin in which the polyketide chain is reduced at five sites by a trans-ER (lovC) [6,7] before it is released from the PKS by a trans-thioesterase (LovG) [10]. The Diels-Alder reaction is proposed to occur at the pentaketide stage in lovastatin biosynthesis, and it is therefore possible that fusarielin biosynthesis follows a similar route.…”
Section: Posmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of synthetic biology, reconstruction of biosynthetic pathways in chassis organisms has been proved to be a possible solution to these problems (Ro et al 2006;Galanie et al 2015). The biosynthetic gene cluster and catalytic role of each functional gene product are well characterized for lovastatin (Kennedy et al 1999;Xie et al 2006;Barriuso et al 2011;Xu et al 2013). Previously, we assembled the biosynthetic pathway of lovastatin in the methylotrophic yeast P. pastoris (Fig.…”
Section: Introductionmentioning
confidence: 99%